PENGOLAHAN LINDI (LEACHATE) DARI TPA DENGAN SISTEM KOAGULASI - BIOFILTER ANAEROBIC - Susanto, Joko Prayitno (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2004)
Leachate is the pollutant which contains various kinds of both organic such as some harmful photogenic bacteria’s and parasitic microbes like Sarcoptes sp and inorganic compounds such as ammonia. The leachate can be caused prurity to human skin. Base on data from Piyungan Community Health Centre, Microbes caused the incidence of dermatitis take number 4 from 10-disease rank within 75%. Piyungan Disposal Site has a possiblity to pollute to Opak River. the leachate need to be processed to decrease the MPN, COD, BOD, TSS and Ammonia parameters before it will be polluted of Opak River. The research had been done to process the leachate to decrease the MPN, COD, BOD, TSS and Ammonia parameters with use coagulation - biofilter anaerobic system. Equipment used was consisted of leachate equalisation (catcher) tank; alum and lime solution container; leachate coagulation tank and biofilter anaerobic tank. The research show that there were influence of leachate processing with coagulation and anaerobic biofilter toward the decreasing of MPN, COD, BOD, TSSand Ammonia parameters with 1, 2, and 3 hours detention time.